PERAN THE GLOBAL FUND DALAM ELIMINASI TUBERKULOSIS DI PROVINSI RIAU TAHUN 2023 - Alfarisi, Aryo Rizky; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study provides an in-depth analysis of the role of The Global Fund in supporting the elimination of Tuberculosis (TB) in Riau Province in 2023. Indonesia ranks as the country with the second-highest TB burden in the world after India, and Riau is among the provinces contributing significantly to the national TB case load. This condition is driven by limited access to healthcare services, inadequate local health system capacity, persistent social stigma, and low public awareness regarding TB transmission and treatment. These challenges highlight the importance of international assistance, particularly from The Global Fund, in accelerating efforts toward TB elimination at the regional level. The research employs a descriptive qualitative method through a literature study and document analysis to examine the forms, mechanisms, and impacts of The Global Fund’s interventions in Riau. The analytical framework is supported by Global Governance Theory, which explains the dynamics of multi-actor health governance. The findings reveal that The Global Fund plays a strategic role through financial contributions, capacity-building programs for health workers, provision of diagnostic tools and essential medicines, as well as community-based education and outreach. These interventions contributed to an increase in TB treatment coverage in Riau, reaching 56% in 2023. However, the study also identifies several obstacles, including geographical challenges, limited community engagement, strong societal stigma, and the region’s dependency on international funding and technical support. Keywords: The Global Fund, Tuberculosis, Riau, Global Governance.